Spring Persistence with Hibernate - Fisher, Paul Tepper; Murphy, Brian D.; Anglin, Steve; Welsh, Tom.; Beckner, Mark.; Buckingham, Ewan.; Cornell, Gary.; Gennick, Jonathan; Hassell, Jonathan; Lowman, Michelle; Moodie, Matthew; Parkes, Duncan; et al. (Berkeley, CA : Apress, 2010)
Persistence is an important set of techniques and technologies for accessing and transacting data, and ensuring that data is mobile regardless of specific applications and contexts. In Java development, persistence is a key factor in enterprise, e-commerce, and other transaction-oriented applications. Today, the Spring framework is the leading out-of-the-box solution for enterprise Java developers; in it, you can find a number of Java Persistence solutions. This book gets you rolling with fundamental Spring Framework 3 concepts and integrating persistence functionality into enterprise Java applications using Hibernate, the Java$1!" (BPersistence API (JPA) 2, and the Grails Object Relational Mapping tool, GORM. Covers core Hibernate fundamentals, demonstrating how the framework can be best utilized within a Spring application context Covers how to use and integrate JPA 2, found in the new Java EE 6 platform Covers how to integrate and use the new Grails persistence engine, GORMs
Architecting Your Application with Spring, Hibernate, and Patterns -- Spring Basics -- Basic Application Setup -- Persistence with Hibernate -- Domain Model Fundamentals -- DAOs and Querying -- Transaction Management -- Effective Testing -- Best Practices and Advanced Techniques -- Integration Frameworks -- GORM and Grails -- Spring Roo.
Keywords: Computer science; Computer Science; Computer Science, general